A Review of Herbicide Resistance in Iran. Issue 4 (December 2016) - Gherekhloo, Javid; Oveisi, Mostafa; Zand, Eskandar; De Prado, Rafael
Abstract : Continuous use of herbicides has triggered a phenomenon called herbicide resistance. Nowadays, herbicide resistance is a worldwide problem that threatens sustainable agriculture. A study of over a decade on herbicides in Iran has revealed that herbicide resistance has been occurring since 2004 in some weed species. Almost all the results of these studies have been published in national scientific journals and in conference proceedings on the subject. In the current review, studies on herbicide resistance in Iran were included to provide a perspective of developing weed resistance to herbicides for international scientists. More than 70% of arable land in Iran is given over to cultivation of wheat, barley, and rice; wheat alone covers nearly 52%. Within the past 40 years, 108 herbicides from different groups of modes of action have been registered in Iran, of which 28 are for the selective control of weeds in wheat and barley. Major resistance to ACCase-inhibiting herbicides has been shown in some weed species, such as winter wild oat, wild oat, littleseed canarygrass, hood canarygrass, and rigid ryegrass. With respect to the broad area of wheat crop production and continuous use of herbicides with the sole mechanism of action of ACCase inhibition, the provinces of West Azerbaijan, Tehran, Khorasan, Isfahan, Markazi, and Semnan are at risk of resistance development. In addition, because of continuous long-term use of tribenuron-methyl, resistance in broadleaf species is also being developed. Evidence has recently shown resistance of turnipweed and wild mustard populations to this herbicide. Stable monitoring of fields in doubtful areas and providing good education and training for technicians and farmers to practice integrated methods would help to prevent or delay the development of resistance to herbicides.